Causal Factors of innovation management that affecting the Farmers Performance - Pimonratanakan, Sudarat (Journal of Humanities and Social Sciences Thonburi University, 2024)
This research aimed 1) to study the causal factors affect Innovation management and Farmers performance. 2) To study the influence of causal factors on Innovation management affects the Farmers performance. 3) To study guidelines for Innovation management that affects the operations of farmers to lead to the creation of policy recommendations for farmers the country. This research is mixed method research. The sample is used in the farmers, consisting of 340 places. The research instrument was a questionnaire and qualitative research using phenomenological methods. From in-depth interviews with 15 farmers. The statistics used in the assumptions Structural Equation Analysis (SEM), research results found that 1) Innovation management has a positive direct influence on competitive advantage 2) Innovation management has a positive direct influence on Farmer performance 3) Competitive advantage has a positive direct influence on Farmers performance 4) Increasing competitive potential has a positive direct influence on Innovation management 5) Creating added value has a direct and positive influence on Innovation management. Confirmatory factor analysis found that hypothesized model is consistent with the model has high accuracy. Considered from x^2 = 76.13, p-value = 0.11 and the CFI = 1.00. The benefit of this research can be to explain the innovation management that affect farmers’ performance. The results of the study can be used in management as a guideline for managing innovation and technological progress. Businesses need to adapt and respond to changes in the environment in order for the business to survive, grow steadily and be able to compete in international markets. Which leads to good results for the organization in the future.